A randomized controlled trial of unguided internet cognitive-behavioral treatment for perfectionism in individuals who engage in regular exercise - Valentine, E.; Bodill, K.; Watson, H.; Hagger, Martin; Kane, Robert; Anderson, Rebecca; Egan, Sarah (John Wiley & Sons, Inc., 2018)
© 2018 Wiley Periodicals, Inc. Objective: Clinical perfectionism has been found to be a risk and maintaining factor in eating disorders (EDs), compulsive exercise, and athlete burnout. This study investigated whether an unguided internet cognitive-behavioral treatment (ICBT) for perfectionism would reduce ED pathology, compulsive exercise, and burnout in individuals who engage in regular exercise. Method: Participants were randomly allocated to intervention (n=38) or waitlist control (n =29). A generalized linear mixed model (GLMM) analysis was conducted pre and post treatment. A follow-up analysis was conducted with the intervention group at 3 and 6 months. Results: The intervention group experienced a significant reduction in perfectionism (FMPS-CM: F[1,117]=17.53, p =<.001, Cohen's d=.82), ED symptomology (EDE-Q: F[1,55]=7.27, p=.009,Cohen's d=.53) and compulsive exercise (CET: F[1,116]=10.33, p<.001,Cohen's d=.63). The changes attained post-treatment were maintained within the intervention group at 3-month (FMPS-CM (t[1,100]=3.67, p<. 001, Cohen's d=.85) (EDE-Q (t[1,50]=2.20, p=.03, Cohen's d=1.26) and 6-month follow-up (FMPS (t[1,100]=2.74, p=007, Cohen's d=.70) (EDE-Q (t[1,50]=2.18, p=.03, Cohen's d=1.26). Discussion: The results indicate unguided ICBT for perfectionism can have a significant impact on perfectionism, compulsive exercise, and ED symptomatology.